2021
DOI: 10.1021/acsnano.0c10344
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Sub-60 Millivolts/Decade Switching in a Metal–Insulator–Metal–Insulator–Semiconductor Transistor without a Ferroelectric Component

Abstract: Negative capacitance field-effect transistors (NC-FETs) have attracted wide interest as promising candidates for steep-slope devices, and sub-60 mV/decade switching has been demonstrated in NC-FETs with various device structures and material systems. However, the detailed mechanisms of the observed steep-slope switching in some of these experiments are under intense debate. Here we show that sub-60 mV/decade switching can be observed in a WS2 transistor with a metal-insulator-metal-insulatorsemiconductor (MIMI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In addition, the I ON / I OFF ratio may also be improved. Similar interpretations can be found in the literature, for example, where the ferroelectric element is replaced by a leaky insulator or where the change in polarization is considered to bring a faster modification of the surface potential compared to modification of the voltage gate as an alternative explanation for demonstrating the sub-60 mV/decade S factor in FETs …”
Section: Resultssupporting
confidence: 82%
“…In addition, the I ON / I OFF ratio may also be improved. Similar interpretations can be found in the literature, for example, where the ferroelectric element is replaced by a leaky insulator or where the change in polarization is considered to bring a faster modification of the surface potential compared to modification of the voltage gate as an alternative explanation for demonstrating the sub-60 mV/decade S factor in FETs …”
Section: Resultssupporting
confidence: 82%
“…It is worth noting that, although sub-thermionic limit SS has been achieved by using mica/HZO gate stack, leakage path originating from grain boundary of polycrystalline HZO and/or traps forming at mica/MoS 2 interface will possibly deteriorate the gate leakage. Wu and Appenzeller have shown a sub 60 mV dec −1 SS for a ferroelectric-free WS 2 transistor [34], they attributed steep switching to a structural factor related to a leaky dielectric layer. However, the gate leakage current density (I G ) of 10 −7 μA μm −1 was simultaneously monitored when measuring I DS -V GS curves of the transistor with 2.9 nm mica/15 nm HZO, as shown in figure 4, indicating that overall gate leakage current have greatly been suppressed by the robust dielectric strength of mica and the clean mica/MoS 2 interface [23].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested the use of capacitive devices to enable the development of high-efficiency transistors that can facilitate further miniaturization of microelectronics. To this end, researchers have actively focused on negative capacitors based on ferroelectric materials that show transient negative capacitance during bias-mediated inversion of material polarization. , Although conventional ferroelectric materials do provide a conceptually direct route to negative capacitance, the ultimate limits of miniaturization that may be afforded by these materials is presently unclear, due to crossover to super paraelectric behavior when the domain size decreases below the correlation length for fluctuations. , More recently, the size limitations have been offset in part by the discovery of sliding ferroelectricity in two-dimensional compounds. , These materials have been shown to exhibit ferroelectric domain sizes as small as 0.01–1 μm 2 , The emergence of ferroelectric negative capacitors further motivates the search for other capacitive elements for incorporation into electrical circuitry. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…1,12 More recently, the size limitations have been offset in part by the discovery of sliding ferroelectricity in two-dimensional compounds. 11,13 These materials have been shown to exhibit ferroelectric domain sizes as small as 0.01−1 μm 2 12,14−16 The emergence of ferroelectric negative capacitors further motivates the search for other capacitive elements for incorporation into electrical circuitry. 2,3,8,14,17−19 Here, we describe the emergence of photocapacitance in two-dimensional (2D) nanocrystal (NC) assemblies.…”
Section: ■ Introductionmentioning
confidence: 99%